Las lluvias de barro: análisis estadístico de una serie de 43 años en Barcelona - Martín Vide, Javier; Llasat, María Carmen (Geographicalia, 2017)
This work analyses the mud-rains doing: (1) an abstract of the phenomenon principal characteristics; (2) a reflection about the difficulties that its observation and climatological study brings out and. (3) an statistical analysis from the period 1944-1986, corresponding to Barcelona.